2004
DOI: 10.1002/jnr.20053
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous tri‐block copolymer produces recovery from spinal cord injury

Abstract: We have studied the ability of nonionic detergents and hydrophilic polymers to seal permeabilized membranes of damaged cells, rescuing them from progressive dissolution, degeneration, and death. We report that a single subcutaneous injection of the tri-block copolymer, Poloxamer 188 (P188) 6 hr after a severe compression of the adult guinea pig spinal cord is able to: (1). preserve the anatomic integrity of the cord; (2). produce a rapid recovery of nerve impulse conduction through the lesion; and (3). produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 43 publications
1
32
1
Order By: Relevance
“…Although our data and that from other cell culture models (Geddes et al, 2003) suggest a relatively transient change in permeability with membranes resealing spontaneously in less than 1 h, other studies suggest a somewhat longer period of membrane disruption (2-4 h; Ellis et al, 1995). Recently, the study conducted by Borgens et al (2004) in adult guinea pig spinal cord injured with compression showed that subcutaneous injection of P188 after 6 h post-injury provided a significant recovery of spinal cord function. Based on our LDH release data, we considered a 15-min interval after the injury to be a good test for its ability to rescue injured neurons in this model.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Although our data and that from other cell culture models (Geddes et al, 2003) suggest a relatively transient change in permeability with membranes resealing spontaneously in less than 1 h, other studies suggest a somewhat longer period of membrane disruption (2-4 h; Ellis et al, 1995). Recently, the study conducted by Borgens et al (2004) in adult guinea pig spinal cord injured with compression showed that subcutaneous injection of P188 after 6 h post-injury provided a significant recovery of spinal cord function. Based on our LDH release data, we considered a 15-min interval after the injury to be a good test for its ability to rescue injured neurons in this model.…”
Section: Discussioncontrasting
confidence: 45%
“…In a spinal cord compression injury model, P188 administered subcutaneously promoted restoration of cord function (Borgens et al, 2004). As with all therapeutic agents targeted to the brain, adequate delivery to the site of injury will have to be achieved including crossing of the blood brain barrier if injected intravenously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of action underlying polymer-mediated rescue and repair is far from clear (Borgens, 2001(Borgens, , 2003. The AFM will allow us to probe the behavior of polymers like polyethylene glycol (Borgens et al, 2002) and Poloxamer 188 (Borgens et al, 2004) with damaged nerve membranes by directly observing the molecules interaction with the membrane rupture while quantitatively monitoring relevant characteristics such as changes in membrane pressure in contact mode during the repair process. In short, the application of AFM to studies of neurobiology has "barely scratched the surface".…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nature of necrosis, mild surfactants have been used to restore integrity to cells after physical and chemical stresses [4,24]. Specifically, poloxamer 188 (P188) was found to 'save' neurons from early necrosis after severe mechanical loading [2,18]. We recently found that P188 surfactant was able to 'save' chondrocytes from acute necrosis in bovine chondral explants subjected to 25MPa of unconfined compression [25].…”
Section: Introductionmentioning
confidence: 99%